Cue Convergence : Associative Effects on Social Intolerance - Cho, Jaeho and de Zuniga, Homero Gil and Shah, Dhavan V. and McLeod, Douglas M. (Communication Research, 2006)
Studies examining the effects of news cues (i.e., labels used to characterize issue domains and social groups) typically fail to consider the possibility that news stories may contain multiple cues that have interactive effects on audience processing and opinion expression. To test this possibility, the authors conduct a Web survey–embedded experiment that manipulates features of a news report about civil liberties restrictions targeted at Arabs portrayed as either immigrants or citizens and as either extremists or moderates. Hypotheses predict stronger intercorrelations and faster speed of response among a range of social intolerance evaluations when respondents encounter the combination of immigrant and extremist cues. Findings indicate the convergence of immigrant and extremist cues not only yield stronger associations between group evaluations, social intolerance, immigration opposition, and minority disempowerment but also reduce response latencies. The results across these two measures provide support for a theory of associative priming via cue convergence.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjA2Mjg3MDc1